Large-scale analysis of macromolecular crowding effects on protein aggregation using a reconstituted cell-free translation system - Niwa, Tatsuya; Sugimoto, Ryota; Watanabe, Lisa; Nakamura, Shugo; Ueda, Takuya; Taguchi, Hideki (Frontiers in Microbiology, 2015)
Proteins must fold into their native structures in the crowded cellular environment, to perform their functions. Although such macromolecular crowding has been considered to affect the folding properties of proteins, large-scale experimental data have so far been lacking. Here, we individually translated 142 Escherichia coli cytoplasmic proteins using a reconstituted cell-free translation system in the presence of macromolecular crowding reagents (MCRs), Ficoll 70 or dextran 70, and evaluated the aggregation propensities of 142 proteins. The results showed that the MCR effects varied depending on the proteins, although the degree of these effects was modest. Statistical analyses suggested that structural parameters were involved in the effects of the MCRs. Our dataset provides a valuable resource to understand protein folding and aggregation inside cells.